Comparative analysis of the impact of marketing strategies on sports documentary series - Sekulić-Škopić, Lucija; Vukasović, Tina (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2025)
Over time, sport has ceased to be merely entertainment and has become a significant factor influencing the economy. Several important themes related to sports marketing include various tools and strategies, sponsorship and partnerships, and media and digital transformation. Consumer behaviors and the economics of sports and trends also differ. The research area of this paper was to investigate the impact of documentary series about athletes on viewers from a marketing perspective as a new trend in marketing strategies. The study examined how documentary series affect the popularity of athletes and how viewers perceive the emergence of documentary series about athletes as their promotion, whether the audience's perception changes after watching the series, and whether they prefer watching documentary series about individual athletes or sports teams. The effects of different marketing strategies of two documentary series about an individual athlete and a sports team were comparatively analyzed. The research was conducted using a quantitative method, a survey technique with an online questionnaire. The sample was selected by simple random sampling within online sports communities, and the target group consisted of active and former athletes in Croatia. The research covers various aspects of sports marketing and connects the film industry with marketing strategies.
Keywords: sports marketing, athlete branding, documentary series